TINGKAT HUNIAN BABIRUSA SULAWESI DI SUAKA MARGASATWA NANTU - Andrew Leonardo Donsu; Johny S. Tasirin; Reynold Kainde (COCOS, 2022)
Abstract Sulawesi Island has a biodiversity that includes a diversity of endemic flora and fauna that is not found in other areas in Indonesia. One of the endemic animals is the Sulawesi Babirusa (B. celebensis) which is an endemic animal to Sulawesi which is very worried about its population due to illegal hunting and lack of control and conservation management.This study aims to estimate the occupancy rate of sulawesi babirusa and to see its distribution pattern in Nantu Wildlife Reserve. Data collection was done using camera traps that were installed in the Nantu Wildlife Reserve,which were made based on a 2 x 2 km chess board pattern. Camera traps were placed in location babirusa tracks. Analisis showed that there are 3 environmental variables that affect the existence rate of the sulawesi babirusa, which are elevation, distance from river, and distance from village. Based on these data, the ocupancy rate of the sulawesi babirusa is 69% in Nantu Wildlife Reserve. Keywords: ocupancy, sulawesi babirusa, nantu wildlife reserve, camera trap.